An investigation of abrasion and wear characteristics of steel slag and granite ballasts. Issue 1 (17th November 2017) - Esmaeili, Morteza; Yousefian, Kaveh; Asgharzadeh Ghahroudi, Peyman
Abstract : One of the main concerns when using steel slag ballast is its high abrasion and wear in comparison with common stone ballast, which can intensify damage to construction and maintenance machinery. In the present study the abrasion and wear characteristics of both steel slag ballast and granite ballast were experimentally investigated and compared. First, the Los Angeles and micro-Deval tests were carried out, and subsequently micro-Vicker tests were employed to measure hardness. The ratios of the results for steel slag ballast to granite ballast in the above-mentioned tests are 2·5, 0·75 and 0·79, respectively. Furthermore, using X-ray fluorescence and X-ray powder diffraction analyses, the compositions and phases that cause such abrasion behaviour were diagnosed. The wear properties of both materials in contact with a welded tamping tine and cemented carbide of ballast scraper chain finger specimens were determined by employing the dry sand/rubber wheel (DSRW) test (ASTM G 65). Results show that the welded specimen showed a higher wear rate compared with a tungsten carbide specimen within the sliding distance, whereas for granite ballast the wear rate decreased markedly. The wear mechanisms were diagnosed by scanning electron microscope observations on the worn surfaces of the specimens during the wear processes.